'Even in death, we're being denied our place as human beings': Geographic Islamophobia and Muslim Cemeteries in the English-Speaking West. (1st January 2022) - Felepchuk, William; Osman, Muna; Keller, Kimberley
Cemeteries are powerful spatial manifestations of belonging and integration for many marginalized communities, including Muslims in the west. This article examines attempts between 2007 and 2020 to establish Muslim cemeteries in four white, English-speaking, Christian-majority (WEC) countries, and the resulting backlash as a geographic form of Islamophobia. These countries are England, Scotland, Australia, and the United States. By drawing theoretically on the geographies of Muslim minorities, Islamic necrogeographies, and theories of Islamophobia and whiteness, we engage five case studies to provide a detailed examination of the Islamophobic objections to attempts to establish Muslim cemeteries. More specifically, we analyse the discursive strategies contained in the speech of hostile locals as presented in newspaper articles. Our analysis identifies a number of key themes mobilized by cemetery opponents to frame the burial sites as a threat to suburban or rural space, often in environmental terms. This preliminary transnational analysis seeks to begin a discussion of conflicts surrounding Muslim cemeteries and the geographic manifestations of Islamophobia in the context of normative WEC space in the rural and suburban English-speaking west.